Análise da relação entre citocinas, biomarcadores da doença de Alzheimer e declínio cognitivo no líquido cefalorraquidiano de uma amostra de pessoas idosas Brasileiras. - Ivonne Carolina Bolaños Burgos (2024)
Cytokines play an important role in the neuroinflammatory process that is directly related to the physiopathology of Alzheimer's disease. (DA). The continuous interactions between beta amyloid (Aβ) plates, Tau protein and cytokines contribute to promoting the inflammatory state of the brain, accelerate the deposition of Aβ and boost the pathology of Tau protein benefiting cognitive decline. The present study aims to evaluate the relationship between cytokines and the main biomarkers of DA, (Aβ42, pTau, tTau) and the cognitive decline evaluated by the Mini Mental State Examination test (MMSE). A cross-sectional case/control study was conducted in the period from March 2015 to February 2024. One hundred and eight elderly Brazilians were categorized clinically into groups of dementia of the DA (n=54) and non-dementia (n=54). All participants were subsequently subjected to clinical analyses and lumbar puncture for the collection of cerebrospinal fluid (CSF). CSF levels of Aβ, phosphorylated tau (pTau), total tau (tTau) and 27 cytokines were determined using the Luminex xMAP technique. Cytokine levels were compared between groups and predictions and associations between cytokines, DA biomarkers and MMSE were evaluated using multiple linear regression analyses. A network analysis was performed to identify the correlations between the predictor variables for each regression model. We found high levels of G-CSF and MIP1α in the dementia group compared to the non-dementia. IL-13, IP-10 and VEGF showed significant associations with Aβ42, while IL-1ra and IL-4 showed association with pTau. Significant associations were found between tTau and IL-1ra, IL-9, IL-10, MCP-1 and MIP1α. Eotaxin, IL-12, IL-1ra and RANTES demonstrated substantial associations with MMSE scores. The network for Aβ42 showed strong correlation between the cytokines VEGF, IP-10 and IL-13. In the Tau protein network, the pro-inflammatory cytokines MIP1α and IL-9 had strongly correlation with the anti-inflammatory cytokines IL-4 and IL-10. According to the network analysis for MMSE score, eotaxin had a positive significant strong correlation with RANTES and positive mild correlation with IL-12 and pTau. Positive and mild correlation were found between IL-12 with RANTES and IL-1ra. Our findings provide evidence that cytokines play a role in the inflammatory process linked to Aß and Tau pathology. IL-1ra may be compromised mainly in Tau phisiopathology.